White paperboard

By applying oxidized cationized starch with controlled cationization and oxidation levels to the back layer of white paperboard, the issues of paper dust and wastewater treatment loads are addressed, resulting in improved surface strength and reduced environmental impact.

JP2025043602APending Publication Date: 2025-04-01RENGO CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023150983
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-19
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

White paperboard production generates paper dust during handling, leading to printing defects and increased wastewater treatment burdens due to the use of high-carbon footprint additives like polyacrylamide and polyvinyl alcohol.

Method used

Application of oxidized cationized starch with a specific cationization and oxidation degree on the back layer of white paperboard, which improves surface strength, reduces paper dust, and lowers wastewater treatment loads by minimizing additive elution.

Benefits of technology

The use of oxidized cationized starch effectively suppresses paper dust generation, enhances the surface strength of white paperboard, and reduces the organic carbon load in wastewater, thereby alleviating treatment burdens and environmental impact.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025043602000001
    Figure 2025043602000001
Patent Text Reader

Abstract

To find a starch-based compound that reduces a burden on wastewater treatment and has a low viscosity for easily coating on a back layer of white paperboard.SOLUTION: There is provided white paperboard having at least a front layer and a back layer, wherein a coating layer having a pigment is provided on the front layer; the back layer is mainly made of recycled paper pulp; oxidized cationized starch is provided on the back layer; and a degree of cationization of the oxidized cationized starch is 0.010 or more and 0.050 or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] This invention relates to a white paperboard, and more particularly to a white paperboard having an oxidized cationic starch in the back layer. [Background technology]

[0002] White paperboard is widely used as boxes for packaging goods, such as detergent boxes, tissue boxes, etc. White paperboard generally consists of at least two layers, a front layer and a back layer, and in many cases a middle layer is placed between the front layer and the back layer. This front layer uses virgin pulp and recycled paper pulp, and a coating layer containing a pigment such as a white pigment is laminated on the front layer. On the other hand, the middle layer and back layer are mainly made of recycled paper pulp. After papermaking and coating, this white paperboard is stored and transported in rolls or sheets until printing such as offset printing is performed, but since there is a period of time when the coated surface of the front layer and the back layer are in contact under load, some of the fine fibers on the surface of the back layer may fall off when they are peeled off, generating paper dust. This paper dust may cause poor printing during printing or soil the surrounding area.

[0003] In response to this, methods are known for suppressing the generation of paper dust, such as a method of coating the back layer of white paperboard with polyacrylamide or polyvinyl alcohol for the purpose of improving the surface strength of the white paperboard (Patent Document 1), a method of coating with an aqueous composition containing polyvinyl alcohol, starch and a crosslinking agent (Patent Document 2), and a method of coating twice with an aqueous starch solution or coating each with water and an aqueous starch solution (Patent Document 3). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Patent Application Publication No. 11-279985 [Patent Document 2] JP 2011-236516 A [Patent Document 3] JP 2013-204155 A Summary of the Invention [Problem to be solved by the invention]

[0005] Incidentally, white paperboard, including the broken paper generated during production, is collected after use and converted into waste paper pulp by defibration for reuse. During this reuse, papermaking additives such as polyacrylamide, polyvinyl alcohol, and starch blended in the white paperboard are dissolved in the defibration liquid, which places a burden on wastewater treatment. In addition, the papermaking additives remaining when the white paperboard is produced must be treated, and it is preferable to reduce this burden. In particular, compounds derived from fossil fuels such as polyacrylamide and polyvinyl alcohol emit more carbon dioxide during production than starch derived from biomass, and this is a factor that increases carbon dioxide emissions in the supply chain at paper mills that use them. Furthermore, when coating the back layer of a white paperboard, if the viscosity of the coating solution is high, coating may become difficult. Therefore, the object of this invention is not only to switch to a papermaking additive that emits less carbon dioxide, but also to find a starch-based compound that reduces the burden on wastewater treatment and has a low viscosity that makes it easy to coat on the back layer of white paperboard. [Means for solving the problem]

[0006] The present invention has achieved the above object by using specific starches, and the gist of the invention resides in the following [1] to [3]. [1] A white paperboard having at least a surface layer and a back layer, wherein a coating layer containing a pigment is disposed on the surface layer, the back layer is a layer mainly made of recycled paper pulp, and oxidized cationized starch is disposed on the back layer, and the cationization degree of the oxidized cationized starch is 0.010 or more and 0.050 or less. [2] The white paperboard according to [1], wherein the degree of oxidation of the oxidized cationized starch is 5 mEq / 100 g or more and 15 mEq / 100 g or less. [3] The amount of the oxidized cationized starch applied to the back layer is 0.5 g / m 2 More than 1.5g / m2 The white paperboard according to [1] or [2] below. Effect of the Invention

[0007] The white paperboard according to the present invention has a back layer coated with a specific starch to prevent the fine fibers from falling off, and the coating solution has a low viscosity, making the coating easy to carry out. As a result of the coating, the surface strength of the white paperboard is improved and the generation of paper dust from the back layer can be suppressed. Furthermore, even when this white paperboard is disintegrated, certain starches are less likely to dissolve into the disintegration liquid, lowering the TOC (total organic carbon) in the wastewater, thereby reducing the burden on wastewater treatment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] The present invention will be described below. This invention relates to a white paperboard having a backing layer made of a specific starch. <White paperboard> The white paperboard according to the present invention is a paperboard having at least a front layer and a back layer, the front layer or the front layer and the back layer being white. The front layer is a layer formed by mixing virgin pulp and, if necessary, recycled paper pulp, and a coating layer containing a pigment such as a white pigment is applied to the surface of this layer. The back layer is a layer formed by blending 50% by weight or more of recycled paper pulp. Furthermore, the white paperboard may have a middle layer as necessary, and this middle layer is a layer formed mainly of recycled paper pulp. This recycled paper pulp may be deinked or not deinked as appropriate depending on the purpose. As mentioned above, the back layer of this white paperboard is mainly made of recycled paper pulp, and fine fibers may fall off from this back layer, generating paper dust.

[0009] <Specific starches - oxidized cationized starch> The specific starch used in the present invention is a starch that has been oxidized and in which some of the hydroxyl groups have been substituted with cationic groups such as quaternary ammonium groups (hereinafter, may be referred to as "oxidized cationized starch"), which contributes to improving the fixation to pulp.

[0010] This oxidized cationized starch is produced by first oxidizing starch and then cationizing it, which makes it possible to prevent the cationic groups from falling off during the oxidation treatment. The oxidation treatment breaks the carbon chains of the starch, decreasing the weight-average molecular weight and decreasing the viscosity of the paste obtained by gelatinizing the treated starch. The oxidation treatment of starch can be carried out by various methods, for example, a method of treating with an oxidizing agent such as a hypohalite, such as sodium hypochlorite.

[0011] By adjusting the oxidation degree of the oxidized cationized starch, it is possible to adjust the viscosity of the starch coating solution gelatinized by dissolving or suspending it in water, and to improve the coating suitability when the starch coating solution is applied to the back layer of the white paperboard. The oxidation degree of this oxidized cationized starch is preferably 5 mEq / 100 g or more, and preferably 6 mEq / 100 g or more. If it is less than 5 mEq / 100 g, it becomes difficult to sufficiently reduce the viscosity of the starch coating solution, and there is a risk that sufficient coating suitability will not be obtained. Specifically, even if a highly viscous starch coating solution is applied to a white paperboard, the starch is not sufficiently absorbed and spreads over the surface, which may cause leakage from the paper edge, inability to coat a sufficient amount of coating, slow coating speed, and reduced productivity, which may result in insufficient improvement in the surface strength of the white paperboard and difficulty in suppressing the generation of paper dust. On the other hand, the degree of oxidation is preferably 15 mEq / 100 g or less, and more preferably 11 mEq / 100 g or less. If it is more than 15 mEq / 100 g, the viscosity of the oxidized cationized starch will decrease too much, causing the starch coating liquid to permeate into the white paperboard, which may make it difficult to obtain sufficient surface strength.

[0012] If this oxidation degree is satisfied, the viscosity of the oxidized cationized starch, when made into a starch paste solution described below, will be in the range of 2 mPa·s to 15 mPa·s, and when made into a starch coating solution, the starch will exhibit appropriate coating suitability. This viscosity can be measured using a digital viscometer (VISCO-895 manufactured by Atago Co., Ltd.) at a temperature of 60°C and a rotation speed of 60 rpm. The starch paste solution is a paste obtained by dissolving or suspending the oxidized cationized starch in water to a concentration of 5% by weight, and heating at 90°C for 30 minutes or more to gelatinize it.

[0013] Meanwhile, since pulp has anionic properties, cationizing starch (including oxidized starch) contributes to improving the fixation to the pulp. Therefore, even if disintegrated, this (oxidized) cationic starch tends to remain fixed to the pulp, and even if it is detached from the pulp, it tends to be re-fixed. Therefore, when this pulp is reused or discharged from the system, the amount of oxidized cationic starch flowing into the wastewater can be suppressed, which contributes to reducing the load on the wastewater treatment system.

[0014] The degree of cationization (degree of substitution: DS) of the oxidized cationized starch is preferably 0.050 or less, and more preferably 0.045 or less. If it is more than 0.050, the viscosity of the coating liquid increases, which may cause problems such as difficulty in coating. On the other hand, the lower limit of DS is not particularly limited, but from the viewpoint of clearly exhibiting the effect of improving the fixation to pulp, it is preferably more than 0, and is preferably 0.010 or more, and more preferably 0.015 or more. As described in JP 2010-180320 A, the degree of cationization (degree of substitution: DS) of cationized starch is calculated as the addition of glycidyltrimethylammonium to hydroxyl groups of starch using an alkali metal as a catalyst, and indicates the degree of cationization.

[0015] <Coating on the back layer of white paperboard> The starch coating solution of the oxidized cationized starch is generally applied to the back layer of white paperboard using mechanical equipment such as a coater, a size press, or a calendar, but it can also be applied manually using a brush, roller, or the like. The amount of this oxidized cationic starch applied to the back layer of the white paperboard was 0.5 g / m2 in solids. 2 Above 0.8g / m 2 More than 0.5g / m is preferable. 2 If the coating amount is less than 1.5 g / m, sufficient surface strength cannot be obtained, resulting in problems such as being unable to suppress the generation of paper powder. 2 Less than 1.2g / m 2 Less than 1.5g / m is preferred. 2 If the amount is larger, the coating amount increases, the drying load increases, and the productivity decreases. EXAMPLES

[0016] The present invention will be described in more detail below using examples, but the present invention is not limited to the following examples. First, the raw materials and evaluation methods used in the present examples will be described.

[0017] <Ingredients> [White paperboard production] The surface layer (2 layers) is a blend of 60% LBKP (bleached hardwood kraft pulp), 20% NBKP (bleached softwood kraft pulp), and 20% recycled paper pulp, while the middle layer (3 layers) and back layer (1 layer) are a blend of 100% recycled paper pulp (magazines, etc.), and the base paper was made using a 6-layer papermaking machine. After that, a coating liquid consisting of pigment and latex was applied on the surface layer on the machine (solid content: 15 g / m 2 ) and calendered to a basis weight of 310 g / m 2 White board was produced. Meanwhile, in the papermaking process of this machine, specifically in the calender part, a starch coating liquid consisting of oxidized cationized starch used in the examples and comparative examples described later was applied to the back layer of the white paperboard being made. The starch coating liquid consisting of oxidized cationized starch was produced by adding water to the oxidized cationized starch to prepare an aqueous solution or suspension with a concentration of 5% by weight, and gelatinizing the solution at 90° C. for 30 minutes.

[0018] [Starch used] (Oxidized Cationic Starch) Starch 1: SW-6300 manufactured by Sanguan Wongse Industries (hereinafter referred to as "SWI"). Starch 2…SWI: SW-5400 (Oxidized acetylated starch) Starch 3…SWI: SW-0110 Starch 4…SWI: SW-0610 Starch 5…SWI: SW-0420 (cationized starch) Starch 6…SWI: SW-6000 Starch 7…SWI: SW-2000 (Polyvinyl alcohol) PVA…Japan Vinyl Acetate Poval Co., Ltd.: J-Poval JF-17

[0019] <Evaluation method> [Cationization degree (degree of substitution: DS)] As described above, this was calculated based on the addition of glycidyltrimethylammonium to the hydroxyl groups of starch, and was shown as a value indicating the number of moles of cationic groups added per anhydrous monosaccharide unit of starch. Specifically, the nitrogen content (N) weight % of the cationized starch was measured using a CHN elemental analyzer (VARIO ELIII, manufactured by Elementor Japan Co., Ltd.) and calculated according to the following formula. Degree of substitution (DS)=162N / (1400-152N) In addition, "152" is the molecular weight of glycidyltrimethylammonium chloride, and "162" is the molecular weight of the anhydrous monosaccharide unit.

[0020] [Oxidation level] A 0.1N aqueous solution of hydrochloric acid was added to the starch sample, which was then stirred, filtered, washed, and heated at 90°C for 30 minutes to cause gelatinization. The resulting starch paste was titrated with a 0.1N aqueous solution of sodium hydroxide using phenolphthalein as an indicator, and the degree of oxidation was calculated using the following formula. Unmodified starch (unoxidized starch) was used as a blank. Oxidation degree (mEq / 100g) = (sample titration amount - blank titration amount) (ml) x NaOH normality / sample weight (g) x 100

[0021] [viscosity] Water was added to the starch sample to dissolve or suspend it to a concentration of 5% by weight, and the starch was gelatinized by heating at 90°C for 30 minutes. The viscosity of the resulting paste was measured using a digital viscometer (Atago Co., Ltd., VISCO-895) at a temperature of 60°C and a rotation speed of 60 rpm.

[0022] [Dissolution test (TOC measurement)] The white paperboard coated with the starch coating solution obtained in the Examples and Comparative Examples was disintegrated in hot water at 90°C, and the resulting pulp slurry was filtered through glass filter paper (GS-25, manufactured by Advantec Co., Ltd.), and the TOC (total organic carbon) of the filtrate was measured by the following method. ·TOC measurement Measuring equipment: Shimadzu Corporation, TOC-LCPH (680℃ combustion catalytic oxidation method) Measurement conditions: The sample was acidified by adding 1.5% hydrochloric acid, and then aerated (flow rate 80 mL / min) before measurement. The increase in TOC when an uncoated blank was used as a reference was calculated using the following formula and evaluated according to the following criteria. Increase rate (%) = {TOC of sample (mg / L) - TOC of blank (mg / L)} / TOC of blank (mg / L) × 100 Evaluation criteria: ○: The increase rate was 20% or less. △: The increase rate was more than 20% but less than 80%. ×: The increase rate was 80% or more.

[0023] [Printing test (paper dust suppression effect)] The white paperboard coated with the starch coating solution obtained in the Examples and Comparative Examples was cut to a width of 650 mm and a length of 700 mm to obtain 2,500 samples, which were offset printed with black ink with 50% full-surface dots (printing machine: Lithrone S44, manufactured by Komori Corporation). The defect detection rate was calculated from the following formula and evaluated according to the following criteria. Defect detection rate (%) = Number of white spots / Number of white board sheets × 100 Evaluation criteria: ○: The defect detection rate was 30% or less. △: The defect detection rate was more than 30% but less than 60%. ×: The defect detection rate was 60% or more.

[0024] [Examples 1-2, Comparative Examples 1-6] Water was added to the various starches shown in Table 1 to obtain starch solutions or suspensions with a concentration of 5% by weight, which were then gelatinized by heating at 90°C for 30 minutes to obtain starch paste liquid. In addition, in Comparative Example 6, PVA was dissolved by heating at 90°C for 60 minutes to obtain a PVA paste liquid. These paste liquids were used as coating liquids and coated on the back layer of the white paperboard in the calender part of the six-layer papermaking machine on-machine, as shown in the manufacturing method of the white paperboard. The coating amounts (solid content) shown in Table 1 were applied. Using the above-mentioned methods, the oxidation degree and cationization degree of the various starches used were measured, and the viscosity of the resulting coating liquid was also measured. Furthermore, dissolution tests and printing tests were performed using white paperboard coated with these coating liquids. The results are shown in Table 1.

[0025] [Table 1]

[0026] (result) In Examples 1 and 2, which used oxidized cationized starch having a degree of oxidation and degree of cationization within the specified range, the TOC of the filtrate was low, the impact on drainage was suppressed, and the falling off of paper powder during printing was also suppressed. On the other hand, in Comparative Example 1, only oxidation was performed, and the degree of oxidation was too low, so the viscosity was high, the starch coating liquid was not absorbed by the paper, the coating amount was reduced, and the paper dust suppression effect was small. In addition, because cationization was not performed, the TOC was high, and it was found that the impact on wastewater was large. In addition, in Comparative Example 2, the degree of oxidation was too high, so the viscosity was low and the starch coating liquid penetrated into the paper, resulting in little effect in suppressing paper dust. Also, because the paper was not cationized, the TOC was high, which had a large impact on wastewater. Furthermore, in Comparative Example 3, although the paper dust suppression effect was exhibited, the TOC was high and the impact on wastewater was large because cationization was not performed. Furthermore, in Comparative Examples 4 and 5, although the impact on drainage was suppressed, the viscosity was high because the starch coating solution was not absorbed by the paper, reducing the amount of coating, and the effect of suppressing paper dust was small, because the solution was not oxidized. On the other hand, in Comparative Example 6, since PVA was used, the effect of suppressing paper dust was shown, but the TOC was high and it was found that the impact on drainage was large.

Claims

1. In a white paperboard having at least a front layer and a back layer, A coating layer having a pigment is disposed on the surface layer, The back layer is a layer mainly made of recycled paper pulp, The backing layer is provided with oxidized cationized starch; The degree of cationization of the oxidized cationized starch is 0.010 or more and 0.050 or less.

2. 2. The white paperboard according to claim 1, wherein the degree of oxidation of the oxidized cationized starch is 5 mEq / 100 g or more and 15 mEq / 100 g or less.

3. The coating amount of the oxidized cationized starch on the back layer is 0.5 g / m 2 1.5g / m or more 2 The white paperboard according to claim 1 or 2, wherein:

Citation Information

Patent Citations

  • White paper board

    JP1999279985A

  • Coated paperboard

    JP2011236516A

  • Method for producing white paperboard for paper container, and paper container

    JP2013204155A